Uma análise da permanência acadêmica em cursos de predomínio feminino e masculino da Universidade Federal da Paraíba - Carvalho, Rayana Andrade de (2018)
This dissertation analyzes factors of academic permanence in areas of female predominance and male predominance of the Universidade Federal da Paraíba. Through some research on higher education, like the census of higher education of Inep (2013, 2015) and the studies of Braga; Peixoto; Baguthi (2001), Almeida et. al. (2006) and Vargas (2010), it was found that the expansion process experienced by higher education, especially after the 2000s, has seen new processes of inequalities in this area. It is clear that some professional careers are still characterized by the emphatic division of sex, that is, on the one side mostly male careers, and on the other side, mostly careers female, and not coincidentally, are also recognized by the greater social prestige (in the case of areas of male predominance) and of lower social prestige (in the case of areas of female predominance). Based on this reality, and considering the importance of research about academic permanence in the various university daily life, the following question is: does the scenario of socioeconomic and gender inequalities, which pervade some professional careers, reflect in the academic permanence in a differentiated way? To answer this question, we investigated the reality of four UFPB graduate courses that appear in the Inep ranking of the 10 biggest undergraduate courses by sex in Brazil and that are of greater and lesser social prestige, being these: Civil Engineering, Engineering of Production, Nursing and Pedagogy. In the methodological process, some instruments were used, among which: A student permanence evaluation scale, elaborated by Nakamura, Castelo Branco and Jezine (2016), which identified the factors that determine permanence in the two areas investigated (male predominance and female predominance), and semi-structured interviews. 81 questionnaires were collected in the four courses and four interviews were conducted, two women enrolled in the area of male predominance (engineering) and two men enrolled in the female predominance area (Nursing and Pedagogy). At the end of the study it was concluded that the scenario of inequalities in professional careers (socioeconomic and sex) generate processes of student stay differentiated, and that is related to the social prestige of the course and the public that attends it.